Two New Geraghty Type Contractions in Gb-Metric Spaces - Yixiao Wang; Chunfang Chen (Journal of Function Spaces)
In this work, two Geraghty type contractions are introduced in Gb-metric spaces, and some fixed point theorems about the contractions are proved. At the end of this article, a theorem about unique solution of an integral function is proved.